Adapting a country-specific Dragonfly Biotic Index: Framework for seven Central European countries and transboundary pattern analysis - Eva Bílková; Hana Šigutová; Petr Pyszko; Veronika Prieložná; Aleš Dolný (Ecological Indicators)
Freshwater diversity is experiencing a significant crisis due to anthropogenic pressures and climate change, with losses exceeding those in terrestrial ecosystems. The Dragonfly Biotic Index (DBI) offers an effective tool for assessing the health and ecological integrity of freshwater habitats through the presence/absence data of odonate species, which respond diversely to environmental changes. Each species within the assemblage is given a value from 0 to 9, which is based on the sum of three sub-indices, each ranging from 0 to 3: distribution, threat, and sensitivity. Originally developed for South Africa, the DBI has been adapted to few regions worldwide. In this study, we adapted the DBI for individual seven Central European countries (Austria, Czechia, Germany, Poland, Slovakia, Slovenia, and Switzerland) using updated species distribution data, national red lists and sensitivity based on the species affinity to specific habitats and population trends. Furthermore, we analyzed transboundary patterns of species distribution and threat, and tested how the subindices vary based on taxonomic and ecological classification (Zygoptera vs Anisoptera, lotic vs lentic species). Our results revealed significant variation in DBI across countries, emphasizing the importance of country-specific adoptions. Anisoptera exhibited moderate total DBI values, whereas Zygoptera presented either high or low values. Furthermore, lentic species displayed lower sensitivity than lotic species. The newly presented DBI values offer a practical tool for conservation, enabling standardized freshwater health monitoring and guiding efforts across Central Europe. This study underlines the necessity of regularly updating DBI to reflect local ecological conditions, ensuring targeted freshwater conservation strategies.